An audit of primary medical conditions in children admitted to the paediatric intensive care unit of Charlotte Maxeke Johannesburg Academic Hospital - Refiloe Keketso Mopeli; Debbie White; Daynia Ballot (South African Medical Association, 2016)
Background. There is approximately one paediatric intensive care unit (PICU) bed per 22 800 children in SA, making PICU beds a very limited resource. Objectives. To determine the spectrum of medical conditions in children admitted to a PICU, their outcomes, and to compare the number and outcomes of HIV-exposed/infected children v. HIV-unexposed children. Methods. This was a retrospective chart review of children older than 28 days, admitted to Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) PICU for medical conditions from 1 January 2013 to 31 July 2014. Results. There were 883 admissions; 518 (59%) were neonates and 234 (26.5%) were surgical patients, leaving a final sample of 131 (14.8%) children with medical conditions. The median age of children admitted was 3.8 months. Out of 131 children, 44 (34%) were HIV-exposed and 16 (12.2%) had a positive HIV polymerase chain reaction (PCR) result. Lower respiratory tract infections (LRTIs) accounted for two-thirds of all admissions at 84 (64.1%) and were significantly more common in HIV-exposed children (p=0.0005); 32 (24.4%) patients died. HIV-exposed children stayed 3 days longer (p=0.015), were ventilated for 4 more days (p=0.012) and were three times more likely to require high-frequency oscillatory ventilation (p=0.0005) than HIV-unexposed children. Mortality was similar between these two groups. Children confirmed HIV PCR-positive had a significantly longer duration of ICU stay (p=0.03) and ventilation (p=0.006) than those who were exposed but uninfected. Conclusion. There were 883 children admitted in 19 months to CMJAH PICU. A total of 15% of admissions were for medical conditions, two-thirds of which were for LRTIs. One-third of the children were HIV-exposed and had similar outcomes to their unaffected counterparts, although their duration of ventilation and length of stay were longer.